Marriage Dispensations Following the Amendment of Law No. 16 of 2019: A Critical Analysis from the Perspective of Maqashid al-Shari’ah: Dispensasi Nikah Pasca Revisi Undang-Undang Nomor 16 Tahun 2019: Analisis Kritis dalam Perspektif Maqashid Syariah - Roidatus Shofiyah; Atmari Atmari (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This study aims to analyze the regulation of marriage dispensation in Indonesian positive law, examine the concept of marriage dispensation from the perspective of Islamic law, and provide a critical analysis of its judicial practices following the amendment of the Marriage Law. This research is a normative legal study employing statutory and conceptual approaches. Legal materials were collected through library research and analyzed qualitatively using a descriptive-analytical method. The findings indicate that, normatively, the regulation of marriage dispensation in Indonesia has been designed as an exceptional legal instrument aimed at protecting children. However, in practice, there remains a tendency for judges to grant dispensations flexibly, often based on sociological considerations rather than the principle of the best interests of the child. From the perspective of Islamic law, although the term “marriage dispensation” is not explicitly recognized, its conceptual basis can be understood through the principles of maqashid al-shariah, which emphasize public welfare (maslahah) and the prevention of harm (mafsadah). This study concludes that a reconstruction of the concept of marriage dispensation is necessary by integrating positive law and maqashid al-shariah to ensure stronger child protection and long-term welfare.